Effect of Strathclyde police initiative "Operation Blade" on accident and emergency attendances due to assault. Issue 3 (May 1997) - Bleetman, A; Perry, C H; Crawford, R; Swann, I J
Abstract : OBJECTIVE: To review assault victim attendance at the accident and emergency department of Glasgow Royal Infirmary before and after a police initiative to curb knife carrying and tackle violent assaults ("Operation Blade"). METHODS: Assault victim attendance was reviewed for the month before the implementation of Operation Blade and for one month a year later. The number of victims requiring treatment in the resuscitation room for stab wounds before, during, and after Operation Blade was also reviewed as a crude indicator of the frequency of serious assaults in the city. RESULTS: There were no significant differences in the nature or number of assault victims attending this hospital one year after Operation Blade compared with the month before its implementation. Operation Blade reduced the number of serious stabbings for a period of 10 months, but subsequently numbers surpassed those prevailing before its implementation. CONCLUSIONS: Any attempt to combat this complex and multifactorial problem must be addressed through a combined public health and education initiative in conjunction with regular press and police campaigns to achieve a sustained effect.